The Role of Inertinite Characteristics and Coal Porosity of Seam A-1 of Muara Enim Formation in West Merapi, Lahat, South Sumatera, Indonesia - Basuki Rahmad; Budi Prayitno; Susilawati S.S.R; Sugeng; Ediyanto (Journal of Geoscience, Engineering, Environment, and Technology, 2022)
Coal contains a complex network of nano-, meso-, and a macro-pore can store fluids and allow fluids to flow through it. Nanoporosity in coal is primarily a result of molecules that have aromatic molecular structures and have been preserved in coal. Most adsorbate compounds, including gases, are stored here. The study area is located in South Sumatera, West Merapi Area, Lahat Regency. Geologically, the area in South Sumatra Basin belongs to the Middle-Late Miocene Muara Enim Formation. Using the ply-by-ply method, coal samples were taken directly from Seam-A in the coal mine walls outcrop, based on macroscopically determinable lithotype information. During laboratory analyses, coal is microscopically analyzed to determine the amount of porosity, permeability, and vitrinite reflectance. The purpose of this study is to investigate the change in composition and characteristics of inertinite macerals when the porosity value is varied.. Vitrinite content is between 91.00-92.80 %; liptinite 0.90-3.40%; inertinite 3.70-4.80%; mineral matter 0.7%-1.8%. Withh a vitrinite reflectance average of 0.34-0.36%, the variation in composition is an indication of changes in plant communities or coal facies. It is generally classified as sub-bituminous coal (ASTM). Porosity value of seam A upper is 1.9% and seam A lower 1.51%, permeability value seam A upper is 70.1 mD and seam A lower 27.1%. Composition of mineral matter in seam A upper is 0.8% and seam A lower 1.7%. The increasing number of inertinite pore is followed by lower porosity value. The inertinite maceral is predominantly aromatic with a high level of cross-linking, and exhibits a high level of aromatization and condensation. They have the highest carbon and the lowest oxygen hydrogen content. A coal maceral's porosity is composed of void spaces, such as open cell lumens preserved in semifusinite and sclerotinite. The porosity of cleats is the percentage of volume in relation to volume of coal, and the porosity of permeability. In coal, semifusinite has extensive interconnected pores that can form significant conduits for fluid flow.